PROFESIONALISME APARATUR SIPIL NEGARA DALAM MENINGKATKAN KUALITAS PELAYANAN PUBLIK: KAJIAN TEORITIS DAN IMPLIKASI PRAKTIS BAGI REFORMASI BIROKRASI DI ERA DEMOKRASI DAN GLOBALISASI - Jackson Yumame (ADMIN: Jurnal Administrasi Negara, 2025)
The professionalism of the State Civil Apparatus (ASN) is a key pillar in creating an effective, efficient, and public interest-oriented bureaucracy amid the challenges of democracy and globalisation. This study aims to theoretically analyse the relationship between ASN professionalism and improvements in the quality of public services, as well as to examine the practical implications for the implementation of bureaucratic reform in Indonesia. The research method used is a qualitative approach with literature study techniques, which examines various public administration theories such as New Public Management, Good Governance, and Public Service Motivation. The results of the study show that ASN professionalism plays a significant role in strengthening the values of accountability, integrity, and innovation in public services. Professionalism is also a key factor in the success of bureaucratic reform through the implementation of a merit system, capacity building, government digitalisation, and the establishment of an adaptive and ethical work culture. Thus, strengthening the professionalism of ASN not only has an impact on improving the quality of public services, but also on the creation of a democratic, clean, and trustworthy government at the national and global levels.